2017
DOI: 10.1097/lbr.0000000000000321
|View full text |Cite
|
Sign up to set email alerts
|

Intrabronchial Voriconazole is a Safe and Effective Measure for Hemoptysis Control in Pulmonary Aspergilloma

Abstract: Intrabronchial voriconazole instillation seems to be a safe and effective modality for hemoptysis control in pulmonary aspergilloma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…9,12 Very few studies have evaluated the effect of multiple instillations of antifungal agents for hemoptysis control in patient with aspergilloma. 12,15 One patient in our study had recurrence of hemoptysis requiring BAE for hemoptysis control. The recurrence rates of hemoptysis after various procedures have been reported from 24 to 30 % at 12 months.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…9,12 Very few studies have evaluated the effect of multiple instillations of antifungal agents for hemoptysis control in patient with aspergilloma. 12,15 One patient in our study had recurrence of hemoptysis requiring BAE for hemoptysis control. The recurrence rates of hemoptysis after various procedures have been reported from 24 to 30 % at 12 months.…”
Section: Resultsmentioning
confidence: 87%
“…All patients had mild increase in cough immediately after the procedure which did not require any interventions or treatment. Transient post-procedure cough was reported by 46.3% of patients in case series reported by Mohan et al 15 All case reports and case series reported till date have found endobronchial antifungal instillation as a safe procedure. 9,15,17 This study has several limitations.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…For treatment of refractory abscesses, cavities (eg in the lung) or severe haemoptysis from pulmonary aspergilloma in which surgical intervention is not feasible, a drainage (in particular for fungal empyema) as well as a local drug instillation may be considered 321,322 . Here, antifungal preparations (commonly containing AmB preparation or azoles, eg voriconazole) have been used (CIII) 323‐325 . No change to previous AGIHO recommendations.…”
Section: Resultsmentioning
confidence: 99%
“…Anti-fungal medication (voriconazole, itraconazole) also was a safe and effective modality and should be considered if surgery contraindicated [27][28][29]. In the case of both medical and surgical treatment were ineffective or contraindicated in massive hemoptysis due to aspergilloma, intervention treatment was an alternative therapy with the success rate was 40.0% [30].…”
Section: Discussionmentioning
confidence: 99%